Pengaruh Product Market Competition dan Financial Performance Terhadap Financial Distress Pada Perusahaan Manufaktur - Renal Yanuardi; Bahtiar Usman (HK-Publishing, 2022)
AbstractThis study aims to analyze the effect of product market competition and financial performance on financial distress in manufacturing companies. The data used in this study is secondary data sourced from the annual reports of manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the 2015-2020 period. The research sample was selected using purposive sampling method in order to obtain 10 companies as samples. Data analysis used to test the hypothesis is multiple regression analysis using E-views 9 software. The independent variables studied were product market competition and financial performance. Controlling variables studied include firm value, leverage and exchange rate risk. The results showed that firm value had a positive effect on financial distress. Other variables such as product market competition, financial performance, leverage and exchange rate risk have no effect on financial distress. This research is expected to be taken into consideration by management and investors for firm value to minimize financial distress in the company.Keywords : product market competition; financial performance; firm value; leverage; exchange rate risk; financial distress AbstrakPenelitian bertujuan untuk menganalisis pengaruh product market competition dan financial performance terhadap financial distress pada perusahaan manufaktur. Data yang digunakan dalam penelitian merupakan data sekunder yang bersumber dari laporan tahunan perusahaan manufaktur yang tercatat di Bursa Efek Indonesia (BEI) selama periode 2015-2020. Sampel penelitian dipilih menggunakan metode purposive sampling sehingga diperoleh 10 perusahaan yang menjadi sampel. Analisis data yang digunakan untuk uji hipotesis adalah analisis regresi berganda dengan menggunakan software E-views 9. Variabel bebas yang diteliti adalah product market competition dan financial performance. Variabel pengendali yang diteliti meliputi firm value, leverage dan risiko nilai tukar. Hasil penelitian menunjukan bahwa firm value memiliki pengaruh positif terhadap financial distress. Variabel lain seperti product market competition, financial performance, leverage dan risiko nilai tukar tidak memiliki pengaruh terhadap financial distress. Penelitian ini diharapkan dapat dijadikan bahan pertimbangan manajemen maupun investor untuk firm value untuk meminimalisir financial distress pada perusahaan.Kata Kunci : persaingan pasar produk; kinerja keuangan; nilai perusahaan; manfaat; risiko, nilai tukar; kesulitan keuangan